Prevalence and pattern of energy drink intake among Australian adolescents. Issue 2 (22nd August 2020) - Trapp, G.; Hurworth, M.; Christian, H.; Bromberg, M.; Howard, J.; McStay, C.; Ambrosini, G.; Martin, K.; Harray, A.; Cross, D.; Oddy, W.; Hammond, D.
Abstract: Background: Energy drinks (ED) are popular among young people despite evidence of associated health risks. Research into the prevalence and pattern of ED intake among young people is sparse. The present study investigates the prevalence and pattern of ED intake among a large sample of adolescents, including how many consume them, how often, for what reasons and in what contexts. Methods: In 2018, all students in grades 7–12 attending 25 randomly selected Western Australian schools were invited to complete an online self‐report survey about EDs. Results: Of the 3688 respondents, 51.2% reported consuming an ED. Of these 'ever consumers', 23.4% drank them monthly, 19.2% weekly and 2% every day. The average age of first intake was 10.7 years. One‐fifth (19.7%) of 'ever consumers' reported consuming more than two EDs in 1 day. Reasons for ED use included taste, to boost energy levels, sport performance and studying. Conclusions: The findings add to limited international evidence about adolescent ED use and provide valuable information to help ensure interventions to reduce intake address the underlying reasons and contexts of ED consumption.